Fully Manual Pineapple Collector Tool - Muhammad Imran Mazlan; Muhammad Hamiemi Harun; Muhammad Hakimie Sudirman; Mohamad, Mahmod Abd Hakim; Nurfarahin Onn (Multidisciplinary Applied Research and Innovation, 2024)
Pineapple (Ananas comosus) in the Bromeliaceous family is a large, succulent, and tasty fruit with immense health benefits. Among all the cultivation activities of pineapple, harvesting is the most difficult, time-consuming, and energy- intensive process due to the higher plant density and spiny leaves of pineapple plants. Although many types of pineapple collecting tools are available in the market, they are mainly for large-scale pineapple plantation operators, and the cost is very expensive. Until now, no research study has been conducted about developing a device to harvest pineapple in Malaysia. This project aims to design and develop a tool that could help in pineapple harvesting, from cutting the pineapple fruit from its plant to picking the pineapple fruit from its plant. The project will mainly focus on helping small-scale pineapple farmers. The tool’s operation will be manually operated as it is easier to use and manufacture.